Nesting biology of Trypoxylon (Trypargilum) lactitarse Saussure (Hymenoptera, Crabronidae) in trap-nests in Southern Brazil - Buschini,M. L. T. (2006)
This study was carried in the Parque Municipal das Araucárias in the municipality of Guarapuava, state of Paraná, Southern Brazil. Three hundred and sixty five nests of T. lactitarse were obtained using trap-nests of 0.7, 1.0, and 1.3 cm in diameter. All of them had similar architecture, regardless of the diameter of the trap-nest. Completed nests consisted of a linear series of brood cells whose average number per nest was of 3.3, 4.0 and 3.6 for the nests with 0.7 cm, 1.0 cm and 1.3 cm in diameter, respectively. They were constructed more often during the summer. T. lactitarse had two types of life cycles: direct development (without diapause), and delayed development (with diapause during winter). Natural enemies included Chrysididae, Sarcophagidae, Dolichopodidae and Ichneumonidae. Out of 1,353 identified spider prey, 1,313 belonged to the Araneidae family.